Answer:
Andrew
Step-by-step explanation:
Abby:
Since red cards are negative, a red 9 would represent the number -9. And because black cards are positive, a black 6 would represent the number 6. To get the sum, we add the two numbers together:
-9 + 6
That gives us a total of -3.
Ashley:
We can do the same thing as before. A black seven would represent 7 and a red 8 would represent -8. Next we again add them together:
7 + (-8)
That gives us a total of -1.
Andrew:
The red 4 is -4, while the black 4 is 4:
-4 + 4
That gives us a total of 0.
Anna:
Anna has a red 8 which represents -8 and another red, a three, which would represent -3. We can add the two to get:
-8 + (-3)
That gives us a total of -11.
In all, Andrew has the highest sum of 0, which means he won the game.
Answer:
300 Square feet
Step-by-step explanation:
Susan built a rectangular fence around her swimming pool.
Length=15ft
Width(or Breadth)=10ft
Height=6ft
To solve this, picture a cuboid with the top and bottom open, that is the key to finding the Surface Area of the Fence.
Surface Area of a Cuboid= 2(LW+LH+WH)
However since the top and bottom are open, the Surface Area becomes
Surface Area of the fence= 2(LW+WH)
=2((15X6)+(10X6)
=2(90+60)=2 X 150 =300
Susan uses 300 Square feet to build her fence.
Answer:
8. 5/6
9. 6.25 or 6 1/4
10. 14.4 Fish
Step-by-step explanation:
8. Reduce the fraction. (20/24) You can divide both the numerator and denominator by 4.
9. Divide 75 by 12
10. Divide 72 by 5
To find the perimeter it is 2 X Width + 2 X the length = 84
32+ 2 X the length = 84
2 X the length = 52
Therefore the length is 26cm
Answer:
x^4-3x^3+x^2-4
Step-by-step explanation:
Given the following functions
R(x) = 2x^4 – 3x^3 + 2x – 1 and
C(x) = x^4 – x^2 + 2x + 3
We are to find the profit function P(x)
P(x) = R(x) - C(x)
P(x) = 2x^4 – 3x^3 + 2x – 1 - ( x^4 – x^2 + 2x + 3)
P(x) = 2x^4 – 3x^3 + 2x – 1 - x^4 + x^2 - 2x - 3
Collect the like terms
P(x) = 2x^4-x^4-3x^3+x^2+2x-2x-1-3
P(x) = x^4-3x^3+x^2+0-4
P(x) = x^4-3x^3+x^2-4
Hence the required profit function P(x) is x^4-3x^3+x^2-4